The Effect of Different Starter Cultures on the Fermentation of Yogurt Added with Aqueous Extract of White Oyster Mushroom (Pleurotus ostreatus) - Sjaloom Sakul; Djalal Rosyidi; Lilik Eka Radiati; Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2020)
The objective of this study was to evaluate the effect of different starter cultures on the fermentation of yogurt added with aqueous extract of white oyster mushroom (Pleurotus ostreatus) whether each starter culture respond differently. This study used a completely randomized design (CRD) with 3 treatments and 4 replications. Yogurt was made with one of the starter cultures as treatment: Streptococcus thermophilus (ST), Lactobacillus acidophilus (LA), or Lactobacillus bulgaricus (LB). Data were analyzed using analysis of variance followed by the least significant difference test. The variables tested were pH, total acid content, viscosity and total lactic acid bacteria. The results showed that yogurt made with ST had lower pH and total acid than the others. The use of LB resulted in higher total acid content. The addition of different starter cultures in yogurt did not influence viscosity. Among starter cultures, the use of LA resulted in higher total lactic acid bacteria (LAB) than the others. However, the number of LAB from different treatments were not much different (within the range of 7 log CFU/mL). It is suggested that the three starter cultures are adaptive and capable to fermenting yogurt added with aqueous extract of white oyster mushroom (Pleurotus ostreatus).Â